Straight outta Dodge City - Boop, David (Baen, 2021)
It?s the final showdown between heroes and darkness in the Old West. Humans versus monsters. Supernatural beings versus greater evils?with a dinosaur or two thrown in for fun. Come explore the untold myths of the West?but no dying on the trail! Joe R. Lansdale takes us on a train ride of the damned in hopes of rescuing one innocent soul. Mercedes Lackey?s duty-bound man races to claim sacred land. Jonathan Maberry introduces us to a half-Comanche hired gun running out of time against some murderous ghosts. And James A. Moore pits skinwalker against kachina in a Western anthology any historian would love! These and a whole passel of other great tales of Western weirdness by Joe R. Lansdale, Mercedes Lackey, Jonathan Maberry, James A. Moore, Harry Turtledove, James Van Pelt, Ava Morgan, Sam Stone, Eytan Kollin, Julie Frost, Kim May, Irene Radford, David Boop, and Tex Thompson!